1984
DOI: 10.1159/000238292
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Metronidazole and Its Main Metabolite in Patients with Active Crohn’s Disease: Correlation with Disease Activity and Therapeutic Efficacy?

Abstract: Serum concentrations of metronidazole and its main metabolite [1-(2-hydroxyethyl)-2-hydroxymethyl-5-nitroimidazole] have been determined by high performance liquid chromatography in sera of 10 patients with histologically confirmed ileocolitis Crohn, 7 presenting with highly active disease and pathologically increased Crohn’s disease activity index (CDAI) and 3 with secreting fistulas but normal CDAI. Metronidazole serum concentrations showed dose-dependent peak characteristics and ranged between 10.62 ± 0.95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…4). According to previous reports, concentration of metronidazole reaches 10.62-24.88 µg/ml in serum after a 1,000 mg/day dose [50]. Therefore, our study suggests that the used metronidazole concentration in this study was su cient to reduce side effects and resistance concerns while offering enhanced antiparasitic activity when combined with alloferon.…”
Section: Discussionsupporting
confidence: 64%
“…4). According to previous reports, concentration of metronidazole reaches 10.62-24.88 µg/ml in serum after a 1,000 mg/day dose [50]. Therefore, our study suggests that the used metronidazole concentration in this study was su cient to reduce side effects and resistance concerns while offering enhanced antiparasitic activity when combined with alloferon.…”
Section: Discussionsupporting
confidence: 64%
“…In 10 patients with active Crohn's disease both the serum metronidazole Cmax and the serum concentration of the hydroxy metabolite were propor- tional to the 400 and 1000mg doses administered (Schneider et al 1984). The investigators also suggested a possible correlation between the disease activity index and mean serum drug concentrations.…”
Section: Enteric Diseasementioning
confidence: 97%